A study on the impact of family planning on population, poverty and economy - Clemente, Anne Melody M.; Montino, Julie Anne G.
For so many years, the Philippines had experienced a rapid growth in its population. This growth is said to be the primary reason why poverty, unemployment and slow economic growth exists. Because of such problems arising in our country, family planning has been introduced and established as response in order to reduce the population growth. The government made ways to implement programs for family planning so as to help people and the country with the arising problem that it encounters. This study is a big help to enlighten the readers on how family planning will be a solution to help our present economic situation. It will also make the readers more aware of proper family planning uses, and its relationship to increasing the family's well-being as well as the society as a whole. Through proper population policy, the Philippines may have a huge step on improving the country of its problems regarding population, poverty and economic growth. Public awareness will lead to a more prosperous response to such problems.